Tiếp tục:\(-A=\frac{x^3+y^3+z^3}{2xyz}\)
thay(1) vào A ta có
\(-A=\frac{y^3+z^3-\left(y+z\right)^3}{2xyz}=\frac{y^3+z^3-y^3-z^3-3yz\left(y+z\right)}{2xyz}\)
\(-A=\frac{3xyz}{2xyz}=\frac{3}{2}\Rightarrow A=\frac{-3}{2}\)
P/s tham khảo bài mình nhé nhớ
ta có:\(x+y+z=0\) \(\Rightarrow x=-\left(y+z\right)\)
\(\Rightarrow x^3=-\left(y+z\right)^3\left(1\right)\)\(;x^2=\left(y+z\right)^2\)
\(\Rightarrow y^2+z^2-x^2=-2yz\)
CMTT:\(z^2+x^2-y^2=-2xz;x^2+y^2-z^2=-2xy\)
thay vào A ta có:
\(A=\frac{-x^2}{2yz}+\frac{-y^2}{2xz}+\frac{-z^2}{2xy}\)